Spousal Age Difference and Mental Health by Sex: Korean Survey Results - Kim, Ji-Su; Kim, Hyejin (Journal of Ecohumanism, 2024)
Purpose: Problems in marital relationships due to age gap between a couple may lead to depression and other mental health issues. However, there is a lack of studies that investigated the association between age gap in couples and mental health. Therefore, this study aimed to identify the relationship between spouse age differences and mental health.Methodology: The data of 7,454 couples from the 2008 and 2012 Korean National Health and Nutrition Examination Surveys were used. Multiple logistic regression analysis was performed.Findings: Women who were ≥10 years older or younger than their husbands displayed poor mental health. Odds ratios (ORs) for women who were ≥10 years younger were 1.72, 1.77, 2.24, and 1.69 for stress perception, depression experiences, depression diagnosis, and suicidal ideation, respectively. Furthermore, in women who were older than their husbands, the ORs for cognition of stress and suicidal ideation were 1.32 and 1.41, respectively.Conclusion: These findings support the development of mental health programs and couples’ education via national promotions and projects. Managing women's mental health in couples with large age gap groups could contribute to family stability and reduce divorce rates.